Methane Production from the Digestion of Thermally Treated Food Waste at 80°C - Fadzil, Farizah; Fadzil, Farihah; Sulaiman, Siti Mariam; Shaharoshaha, A'isyah Mardhiyyah; Seswoya, Roslinda (Dorma Journals, 2020)
Food waste is the most suitable feedstock for anaerobic digestion. However, methane yield from the digestion of food waste is low. Therefore thermal pretreatment serves as the best solution. Also, the effect of thermal pretreatment on food waste (Malaysian dietary) before anaerobic digestion has low documentation. Hence this research aims to analyze the methane production and its kinetics from the digestion of thermally treated food waste. The result showed that thermal treatment improves the bioavailability of food waste, subsequently improve the methane production of food waste. The ultimate methane yield for thermally treated food waste at 80°C was 883.08 CH4/gVS higher than untreated food waste. The kinetic parameters observed from Modified Gompertz modeling were slightly lower from the laboratory data for both substrates. Thus, thermal pretreatment undoubtedly improved the anaerobic digestion of food waste.